2014
DOI: 10.3224/zff.v26i1.15914
|View full text |Cite
|
Sign up to set email alerts
|

“Somebody is thinking about it”: Women as household managers in dual-earner families

Abstract: In this work we focus, through a multi-method approach, on the managerial practices used by working mothers to deal with complex schedules and family needs in domestic life. We know, from previous studies, that dual earner families face substantial reorganizations of their domestic life, but there has been little research on how such reorganizations are accomplished within families. Findings draw on different data sets (focus groups, self-report charts, naturally occurring interactions) and, overall, show the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…However, the mothers confirmed that the father figure was involved more in affective and emotional dimensions, for example, with bedtime routines and games; this is consistent with recent researches realized in Italian context with working mothers and fathers (Alby & Di Pede, 2014;Alby, Fatigante, & Zucchermaglio, 2014). These results prefigure one area that is associated with affective father figures that in the scientific literature is generally associated with the role of the mother (Scabini & Cigoli, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…However, the mothers confirmed that the father figure was involved more in affective and emotional dimensions, for example, with bedtime routines and games; this is consistent with recent researches realized in Italian context with working mothers and fathers (Alby & Di Pede, 2014;Alby, Fatigante, & Zucchermaglio, 2014). These results prefigure one area that is associated with affective father figures that in the scientific literature is generally associated with the role of the mother (Scabini & Cigoli, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…The survey design also limits available measures for women's time use; because the CDS time diaries were designed to capture children's daily activities, no information is available on mothers' activities when children are not directly engaged. Previous studies indicate such care work is a substantial task for many women (Alby, Fatigante, and Zucchermaglio 2014;Randles 2021), and it remains unclear if certain latent classes invest more time into this type of labor than others. These problems would ideally be fixed with tailored questions added to existing social surveys or new, large-scale surveys that are designed to measure intensive mothering across demographic groups.…”
Section: Resultsmentioning
confidence: 99%
“…The survey design also limits available measures for women’s time use; because the CDS time diaries were designed to capture children’s daily activities, no information is available on mothers’ activities when children are not directly engaged. Previous studies indicate that such care work is a substantial task for many women (Alby, Fatigante, and Zucchermaglio 2014; Randles 2021), and it remains unclear whether certain latent classes invest more time in this type of labor than others. These problems would ideally be fixed with tailored questions added to existing social surveys or with new, large-scale surveys that are designed to measure intensive mothering across demographic groups.…”
Section: Discussionmentioning
confidence: 99%